Eight Universities To Have Gap Year Program For Students - See Hua, Daily News (Kuching) (See Hua Daily, 2017)
城 德利g尤索 宣沛，今年 9月起国内 8所国立大 学，将正式 落实空档年 计划（Gap Year Progra m ) ' ih 大 学生能在 公共机构进 行志工服务 以及累计运、